2016
DOI: 10.1021/acschemneuro.6b00059
|View full text |Cite
|
Sign up to set email alerts
|

C-Glycosylflavones Alleviate Tau Phosphorylation and Amyloid Neurotoxicity through GSK3β Inhibition

Abstract: Alzheimer's disease (AD) is the most common brain disorder worldwide. Aberrant tau hyperphosphorylation and accumulation play critical roles in the formation of neurofibrillary tangles highly associated with neuronal dysfunction and cognitive impairment in AD pathogenesis. Glycogen synthase kinase-3β (GSK3β) is a key kinase responsible for tau hyperphosphorylation. Selective inhibition of GSK3β is a promising strategy in AD therapy. Corn silks (CS, Zea mays L.) have been traditionally used as a medicinal herb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 54 publications
7
71
0
Order By: Relevance
“…GSK3β is an imperative regulator of amyloidogenic processing of βAPP and tau hyperphosphorylation, and its inhibition reduces Aβ and tau pathology . In this context, our results first demonstrated that Aβ 42 activated GSK3β by decreasing its phosphorylation, which was prevented by melatonin pretreatments in a receptor‐dependent manner.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…GSK3β is an imperative regulator of amyloidogenic processing of βAPP and tau hyperphosphorylation, and its inhibition reduces Aβ and tau pathology . In this context, our results first demonstrated that Aβ 42 activated GSK3β by decreasing its phosphorylation, which was prevented by melatonin pretreatments in a receptor‐dependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…59,60 GSK3β is an imperative regulator of amyloidogenic processing of βAPP and tau hyperphosphorylation, 14,61 and its inhibition reduces Aβ 15 and tau pathology. 16 In this context, our results first demonstrated that Aβ 42 activated GSK3β by decreasing its phosphorylation, which was prevented by melatonin pretreatments in a receptor-dependent manner. Because alterations in GSK3β activity could lead to changes in PS1 function [62][63][64] and GSK3β is also involved in regulating BACE1 15 and NF-κB activity, 65 using ARA (GSK3β inhibitor) data justified GSK3β-dependent regulation of BACE1 and PS1 under pathological conditions because blocking GSK3β resulted in partial inhibition of the Aβ 42 -induced increase in the levels of BACE1 and PS1 as well as the Aβ 42induced upregulation of pNF-κB/NF-κB.…”
Section: Discussionmentioning
confidence: 60%
“…The flavonoid activities in the central nervous system have been previously reported in the literature (Grosso, Valentão, Ferreres, & Andrade, ). Liang, Zhang, Su, Williams, and Li () described the C‐ glycosyl flavones as a possibility of new lead candidates with a novel mechanism of action for the development of Alzheimer's disease. The antidepressant‐like effects of C‐ glycosyl flavonoids were described for vitexin, underlying its monoaminergic mechanisms (Can, DemirÖzkay, & Üçel, ); and for orientin, with improvement of central oxidative stress, neurotransmission and neuroplasticity (Liu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the The flavonoid activities in the central nervous system have been previously reported in the literature (Grosso, Valentão, Ferreres, & Andrade, 2013). Liang, Zhang, Su, Williams, and Li (2016) described the C-glycosyl flavones as a possibility of new lead candidates with a novel mechanism of action for the development of Alzheimer's disease.…”
Section: Effects Of the Acute Administration Of Enriched C-glycosylmentioning
confidence: 97%
“…In this section, CADD techniques employed for the development of anti-Tau therapeutics are summarized. Molecular docking and enzymatic kinetics demonstrated that C-glycosylflavones selectively inhibited GSK3β-mediated Tau hyperphosphorylation acting as a substrate competitive inhibitor [148]. A group of marine indole alkaloids isolated from the marine tunicate Aplidium were identified as scaffolds for designing new anti-Tau hyperphosphorylation inhibitors using docking and MD simulations [149].…”
Section: Cadd For the Development Of Anti-tau Inhibitorsmentioning
confidence: 99%